2016
DOI: 10.1080/10428194.2016.1263843
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose-escalation study of oral abexinostat for the treatment of patients with relapsed/refractory higher-risk myelodysplastic syndromes, acute myeloid leukemia, or acute lymphoblastic leukemia

Abstract: Phase 1 dose-escalation study of oral abexinostat for the treatment of patients with relapsed/ refractory higher-risk myelodysplastic syndromes, acute myeloid leukemia, or acute lymphoblastic leukemia, Leukemia & Lymphoma, 58:8, 1880-1886, DOI: 10.1080/10428194.2016 Histone deacetylase (HDAC) inhibitor abexinostat is under investigation for the treatment of various cancers. Epigenetic changes including aberrant HDAC activity are associated with cancers, including myelodysplastic syndromes (MDS), acute myeloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Other hydroxamate-based HDACi have been recently tested in clinical studies, such as Givinostat (ITF2357) [176,177,178,179], Resminostat (4SC201) [180], Abexinostat (PCI-24781) [181,182,183,184], Quisinostat (JNJ-26481585) [185], and Pracinostat (SB939) [109,110], with all of them being HDAC pan-inhibitors except for Givinostat, which more specifically targets HDAC1, 2, 3, and 6. However, little information is available regarding AML.…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
See 1 more Smart Citation
“…Other hydroxamate-based HDACi have been recently tested in clinical studies, such as Givinostat (ITF2357) [176,177,178,179], Resminostat (4SC201) [180], Abexinostat (PCI-24781) [181,182,183,184], Quisinostat (JNJ-26481585) [185], and Pracinostat (SB939) [109,110], with all of them being HDAC pan-inhibitors except for Givinostat, which more specifically targets HDAC1, 2, 3, and 6. However, little information is available regarding AML.…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
“…Interestingly, those cell lines positive for AML1/ETO were more sensitive to this inhibitor [186]. In the case of Abexinostat, this HDACi was tested in a phase I trial in AML patients with limited clinical benefit [182]. Pracinostat showed potent efficacy on AML in preclinical studies.…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
“…). (B) karyotype showing 46, XX, t(9;11)(p22;q23) [20] . (C) The blasts percentage changes during different regimens of chemotherapy However, in most patients with PRAME-expressing AML, PRAMEspecific CD8 + cytotoxic T lymphocyte (CTL) response is either undetectable or too weak to exert immune surveillance.…”
Section: F I G U R E 1 (A) Bone Marrow Aspirate Showing Monoblasts (Wmentioning
confidence: 99%
“…In certain types of T-ALL cell lines, such as Notch-driven T-ALL, panobinostat has been shown to induce apoptosis as well as downregulating Myc [ 129 ]. However, a phase 1 trial of the oral HDAC inhibitor abexinostat, including patients with ALL, showed limited efficacy as a single agent [ 130 ]. Combination therapies where an HDAC inhibitor is combined with cytotoxic agents, such as cytarabine, may be more effective as shown in KMT2A -rearranged ALL murine models [ 131 ].…”
Section: Epigenetic Regulators In Allmentioning
confidence: 99%